2021
DOI: 10.3390/ijms22062860
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Regional Blood–Brain Barrier Integrity in Non-Demented Elderly Subjects

Abstract: The role of the blood–brain barrier (BBB) breakdown has been recognized as being important in Alzheimer’s disease pathogenesis. We aimed to evaluate whether regional BBB integrity differed according to sex and whether differences in BBB integrity changed as a consequence of aging or cognitive decline, using dynamic contrast-enhanced (DCE)-magnetic resonance imaging (MRI). In total, 75 participants with normal cognition (NC) or mild cognitive impairment (MCI) underwent cognitive assessments and MRI examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…A difference between sexes in BBB permeability was also confirmed using dynamic contrast-enhanced (DCE)-magnetic resonance imaging (MRI) [ 138 ]. In that study, the authors demonstrated a better BBB integrity in cingulate and occipital cortices in females than in male non-demented elderly subjects.…”
Section: Sex Differences In Mmps and Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A difference between sexes in BBB permeability was also confirmed using dynamic contrast-enhanced (DCE)-magnetic resonance imaging (MRI) [ 138 ]. In that study, the authors demonstrated a better BBB integrity in cingulate and occipital cortices in females than in male non-demented elderly subjects.…”
Section: Sex Differences In Mmps and Pathologiesmentioning
confidence: 99%
“…In that study, the authors demonstrated a better BBB integrity in cingulate and occipital cortices in females than in male non-demented elderly subjects. They also found that this sex-related difference in BBB integrity was attenuated by aging or when cognitive decline occurred, but the difference remained in the occipital cortex independently of these two factors [ 138 ].…”
Section: Sex Differences In Mmps and Pathologiesmentioning
confidence: 99%
“…Despite the limitations of examining a male-only cohort, we believe that the extensive information accumulated from the cohort over the years is valuable for research on ageing and should be utilized. Studies investigating sex differences in BBB permeability in humans are scarce, but some studies have indicated that there may be sex-related differences in BBB permeability [ 60 ]. This should be kept in mind when studying BBB permeability and interpreting findings.…”
Section: Discussionmentioning
confidence: 99%
“…Likely due to the effect of estrogen receptors, it has been shown that women have a stronger resistance against age-related increases in BBB permeability than men until the late life-stage [ 42 ]. After the end of estrogen production, the BBB in the occipital cortex, where the estrogen-producing neurons are highly enriched [ 43 ], becomes more vulnerable in women [ 42 ]. CLDN5 expression is also regulated by circadian rhythms and clock transcription factor brain and muscle aryl-hydrocarbon receptor nuclear translocator like protein 1 (BMAL1); the expression of Cldn5 is higher in the morning and lower in the evening, with rhythmic expression lost in endothelial specific Bmal1 −/− mice [ 44 , 45 ].…”
Section: The Regulatory Mechanisms Of Cldn-5 By Junctional Proteins A...mentioning
confidence: 99%